Utilization of Basil Leaf Extract (Ocimum basilicum L.) as an Alternative to Lowering Formalin Levels in White Tofu - Fadjar Kurnia Hartati; Trivena Trivena (Jurnal Teknologi Hasil Pertanian, 2024)
Tofu is one of the foods that are very liked by the people of Indonesia. However, because it is easily damaged, there are still many tofu manufacturers who use formalin with the aim of extending the shelf life of products and avoiding losses. Based on this, the purpose of this study was to test the effectiveness of basil leaf extract solution with different concentration variations and soaking duration in reducing formalin content in white tofu, as well as observing changes in white tofu protein levels before and after treatment. In addition, the study will also conduct sensory tests of color, suppleness and aroma. This research method applies a factorial Complete Randomized Design (RAL) involving two main factors. The first factor is the concentration of basil extract solution (K), which has three levels (K1:10%, K2:20%, and K3:30%). The second factor is the duration of immersion (L), which also has three levels (L1: 30 minutes, L2: 60 minutes, and L3: 90 minutes). Each variation of the treatment was repeated three times, and tests were carried out on formalin content, protein levels, and sensory tests covering aspects such as color, texture, and aroma. The findings of this study indicate that the ability of the basil leaf extract solution to the highest decrease in formalin was 66.61% and an increase in protein content of 71.19%, namely in the treatment concentration of 30% basil leaf extract solution with immersion time 90 minutes (L3K3), with the results of the sensory test of texture 4.6 (like), color 4.1 (like), and aroma 3 (dislike).